КОМБИНИРОВАННЫЙ МЕТОД КЛАССИФИКАЦИИ ИЗОБРАЖЕНИЙ НА ОСНОВЕ ОБУЧАЕМЫХ ВЕСОВЫХ КОЭФФИЦИЕНТОВ - Сеитназаров, К.К.; Куралбаев, А.О.; Султанбаева, А.Т.; Султанов, Б.К. (SCIENCE and SOCIETY, 2025)
This article proposes a method for interpreting multispectral images based on classification algorithms using wavelet features and their quantization. The features are transformed into binary vectors through value range segmentation, followed by decision-making using class membership estimation. A distinctive aspect of the approach is the introduction of a feature significance indicator that considers the discriminative power of the characteristics and is used both as a selection criterion and as a weighting factor.